Preparation method of zinc-containing ionic liquid, preparation method of Zn-containing multi-layer efficient synergistic flame-retardant epoxy acrylic coating and coating prepared from zinc-containing multi-layer efficient synergistic flame-retardant epoxy acrylic coating
By adding zinc-containing ionic liquid to the epoxy acrylate coating and forming nano ZnO and expanded carbon layer, the flexibility, water absorption and flammability of the coating are solved, and its thermal stability and flame retardant properties are improved, thus achieving Highly efficient transparent fire-resistant coating effect.
Patent Information
- Application Number
- CN202411399745.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
The existing epoxy acrylate coating has problems such as poor flexibility, high water absorption, poor environmental protection performance, poor mechanical properties and flammability during the curing process, which limits its application in high-tech fields, especially in transparent fire-resistant coatings. The flame retardant properties and chemical properties are insufficient to meet current needs.
Zn-containing ionic liquid is combined with epoxy acrylic acid resin to prepare Zn-containing multi-layer, highly efficient synergistic flame-retardant epoxy acrylic acid coating by photocuring. Zn-containing active ionic liquid is synthesized using zinc chloride and acrylamide, and it is cured by UV. The nano-ZnO and expanded flame retardant carbon layer are formed to jointly promote efficient flame retardant.
The thermal stability and flame retardant effect of the coating are improved, forming a mechanism that combines low-temperature expansion flame retardant and high-temperature nanofire retardant, enhancing the comprehensive performance of the coating, and providing a theoretical basis for the design of high-efficiency flame retardant coating.
Smart Images

Figure CN119285487A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of epoxy acrylic resin flame retardant materials, and in particular relates to a Zn-containing multi-layered high-efficiency synergistic flame retardant epoxy acrylic paint. Background Art
[0002] In today's world, with the rapid development of high-tech and the continuous improvement of environmental protection requirements, people's quality of life and lifestyle are undergoing profound changes. In the material world, natural polymer materials and artificially prepared polymer materials have become important driving forces for innovation and environmental protection due to their unique properties and wide applications. Epoxy acrylate (EA) is prepared by ring-opening esterification of epoxy resin and (meth) acrylic acid under the action of a catalyst. It has excellent comprehensive properties and is currently the most widely used and largest amount of photocurable oligomer. It has a wide range of application value and broad market prospects in the field of UV photocurable materials. As a functional coating, the photocurable flame-retardant transparent coating not only has a strong decorative effect, but also has the role of protecting ancient wooden buildings. However, epoxy resin is prone to defects during the curing process. There are shortcomings such as poor flexibility of the cured film, low water absorption, poor environmental performance, poor mechanical properties, and flammability, which limit its application in the field of high technology. Therefore, it is usually modified or other substances are added to improve its protective performance. Domestic research on transparent fire-retardant coatings is mostly limited to flame retardant properties, and there is relatively little research on the effects of the mechanical and chemical properties of the coating on ancient wooden buildings. The price and variety of products cannot meet current needs. Whether a transparent fire-retardant coating with high cost performance, easy construction and superior performance can be developed still requires considerable basic research. Therefore, the performance of EA coatings in the field of flame retardancy has gradually become a new research direction.
[0003] At present, most of the flame retardants commonly used in UV-curing epoxy acrylate (EA) coatings are additive flame retardants, while there are few flame retardants that are liquid at room temperature and have copolymerization activity, especially liquid active flame retardants that can copolymerize with epoxy acrylate and have highly transparent coatings. It is necessary to study and improve them in order to provide a basis for the flame retardant mechanism and the design of efficient flame retardant coatings. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a method for preparing a zinc-containing ionic liquid, a method for preparing a Zn-containing multi-layered high-efficiency synergistic flame-retardant epoxy acrylic coating and the coating.
[0005] One of the technical solutions adopted by the present invention to solve the technical problem is:
[0006] Provided is a method for preparing a zinc-containing ionic liquid. The method comprises: placing acrylamide and p-hydroxyanisole in a round-bottom flask and mixing them evenly; placing the flask in an oil bath; heating the flask to 70-90°C under magnetic stirring conditions until the reactants in the flask are completely dissolved; adding zinc chloride; continuing heating and stirring for 2-4 hours under condensation reflux conditions; adding an acetone solvent; reacting at 60°C for 3 hours; and performing vacuum rotary drying at 60°C after the reaction is completed to obtain a clear and transparent zinc-containing ionic liquid.
[0007] Furthermore, the mass ratio of acrylamide to zinc chloride is 1:1.
[0008] Furthermore, the mass of the p-hydroxyanisole is 0.3% of the mass of acrylamide.
[0009] The second technical solution adopted by the present invention to solve its technical problem is:
[0010] Provided is a method for preparing a Zn-containing multi-layered high-efficiency synergistic flame-retardant epoxy acrylic coating. The method comprises: sequentially stirring the zinc-containing ion liquid obtained by the above-mentioned method for preparing the zinc-containing ion liquid, epoxy acrylic resin, and a photoinitiator, heating and ultrasonically oscillating until bubbles are eliminated, and stirring to form a uniform solution, uniformly coating the prepared uniform solution on a coating carrier, and light-curing to obtain the Zn-containing multi-layered high-efficiency synergistic flame-retardant epoxy acrylic coating.
[0011] Furthermore, the mass ratio of the zinc-containing ion liquid, epoxy acrylate resin, and photoinitiator is 1.0-7.0:4.8-5.2:0.2-0.3.
[0012] The third technical solution adopted by the present invention to solve its technical problem is:
[0013] Provided is a Zn-containing multi-layered high-efficiency synergistic flame-retardant epoxy acrylic coating, which is prepared by the preparation method of the Zn-containing multi-layered high-efficiency synergistic flame-retardant epoxy acrylic coating.
[0014] Compared with the background technology, the present technical solution has the following advantages: the present invention uses zinc chloride and acrylamide as raw materials to synthesize zinc-containing active ionic liquid, and then mixes it with EA and solidifies it into a coating through UV. The results show that Zn(Am)Cl2 has good compatibility with EA coating, and the Zn(Am)Cl2 / EA flame retardant system has good thermal stability. Zn(Am)Cl2 can promote the low-temperature degradation of the coating, which helps to improve the flame retardant effect of the coating; the zinc-containing ionic liquid has the behavior of macroscopic catalytic carbonization at low temperature and microscopic catalytic flame retardancy at high temperature. During the flame retardant process, zinc ions are gradually converted from free state to bound state to form nano ZnO of different morphologies, and a nano flame retardant carbon layer is constructed, which synergistically expands the flame retardant mechanism. The two jointly promote the formation of high-efficiency flame retardant EA coating. The study of the microscopic carbonization process of the flame retardant coating reveals the law of carbonization of the flame retardant catalytic coating, and provides a theoretical basis for the preparation of high-efficiency flame retardant coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0016] Figure 1 It is the NMR spectrum of zinc ionic liquid Zn(Am)Cl2;
[0017] Figure 2 Infrared spectra of ZnCl2, AM, and Zn(Am)Cl2, a-ZnCl2; b-AM; c-Zn(Am)Cl2;
[0018] Figure 3 It is the infrared spectrum of thermal degradation of sample 4 at 25-220°C;
[0019] Figure 4 It is the infrared spectrum of thermal degradation of sample 4 at 230-280°C;
[0020] Figure 5 It is the infrared spectrum of thermal degradation of sample 4 at 290-500°C;
[0021] Figure 6 It is the infrared spectrum of thermal degradation of sample 6 at 25-220°C;
[0022] Figure 7 It is the infrared spectrum of thermal degradation of sample 6 at 230-280°C;
[0023] Figure 8 It is the infrared spectrum of thermal degradation of sample 6 at 290-500°C;
[0024] Fig. 9 is the X-ray diffraction pattern of the carbon layer of sample 6-8 at 500°C;
[0025] Fig.10 is the X-ray diffraction pattern of nano ZnO;
[0026] Fig.11 TG curves of samples 1-8;
[0027] Fig.12 SEM images of the carbon layer of sample 1 at 300 °C, a-250 times, b-250 times, c-500 times, d-2k times;
[0028] Fig.13 SEM images of the carbon layer of sample 1 at 350°C, a-30 times, b-500 times, c-1k times, d-1k times;
[0029] Fig.14 SEM images of the carbon layer of sample 1 at 400°C, a-50 times; b-1k times; c-450 times; d-2k times;
[0030] Fig.15 SEM images of the carbon layer of sample 1 at 450°C, a-250 times; b-250 times; c-500 times; d-2k times;
[0031] Fig.16 SEM images of the carbon layer of sample 1 at 500°C, a-30 times; b-50 times; c-80 times; d-1k times;
[0032] Fig.17 SEM images of the carbon layer of sample 2 at 300°C, a-450 times; b-1k times; c-10k times; d-15k times;
[0033] Fig.18 SEM images of the carbon layer of sample 2 at 330°C, a-300 times; b-3k times; c-10k times; d-10k times;
[0034] Fig.19 SEM images of the carbon layer of sample 2 at 350°C, a-1k times; b-5k times; c-20k times; d-20k times;
[0035] Fig. 20 SEM images of the carbon layer of sample 2 at 370°C, a-150 times; b-500 times; c-1.8k times; d-3.5k times;
[0036] Fig.21 SEM images of the carbon layer of sample 2 at 400°C, a-700 times; b-2k times; c-5k times; d-11k times;
[0037] Fig. 22 SEM images of the carbon layer of sample 2 at 430°C, a-1.1k times; b-5k times; c-15k times; d-10k times;
[0038] Fig.23SEM images of the carbon layer of sample 2 at 450°C, a-150 times; b-600 times; c-900 times; d-1.5k times;
[0039] Fig.24 SEM images of the carbon layer of sample 2 at 470°C, a-1.5k times; b-5k times; c-11k times; d-10k times;
[0040] Fig.25 SEM images of the carbon layer of sample 2 at 500°C, a-500 times; b-2.2k times; c-5k times; d-10k times;
[0041] Fig.26 SEM images of the carbon layer of sample 4 at 180°C, a-100 times; b-1k times; c-3k times; d-20k times;
[0042] Fig. 27 SEM images of the carbon layer of sample 4 at 190°C, a-2k times; b-2k times; c-30k times; d-10k times;
[0043] Fig.28 SEM images of the carbon layer of sample 4 at 200°C, a-3k times; b-5k times; c-35k times; d-30k times;
[0044] Fig.29 SEM images of the carbon layer of sample 4 at 210°C, a-250 times; b-1k times; c-3k times; d-60k times;
[0045] Fig.30 SEM images of the carbon layer of sample 4 at 220°C, a-350 times; b-2k times; c-20k times; d-60k times;
[0046] Fig.31 SEM images of the carbon layer of sample 4 at 230°C, a-250 times; b-2k times; c-5k times; d-15k times;
[0047] Fig.32 SEM images of the carbon layer of sample 4 at 240°C, a-600 times; b-2k times; c-20k times; d-60k times;
[0048] Fig.33 SEM images of the carbon layer of sample 4 at 250°C, a-500 times; b-3k times; c-30k times; d-30k times;
[0049] Fig.34 SEM images of the carbon layer of sample 4 at 260°C, a-1k times; b-2k times; c-10k times; d-80k times;
[0050] Fig.35SEM images of the carbon layer of sample 4 at 270°C, a-1k times; b-10k times; c-50k times; d-80k times;
[0051] Fig.36 SEM images of the carbon layer of sample 4 at 280°C, a-1k times; b-5k times; c-35k times; d-30k times;
[0052] Fig.37 SEM images of the carbon layer of sample 4 at 290°C, a-600 times; b-2k times; c-40k times; d-150k times;
[0053] Fig.38 SEM images of the carbon layer of sample 4 at 300°C, a-800 times; b-2k times; c-3k times; d-40k times;
[0054] Fig.39 SEM images of the carbon layer of sample 4 at 330°C, a-500 times; b-1.5k times; c-45k times; d-80k times;
[0055] Fig.40 SEM images of the carbon layer of sample 4 at 350°C, a-40 times; b-120 times; c-220 times; d-450 times;
[0056] Fig.41 SEM images of the carbon layer of sample 4 at 370°C, a-30 times; b-100 times; c-100 times; d-300 times;
[0057] Fig.42 SEM images of the carbon layer of sample 4 at 400°C, a-60 times; b-500 times; c-600 times; d-700 times;
[0058] Fig.43 SEM images of the carbon layer of sample 4 at 430°C, a-30 times; b-130 times; c-300 times; d-1k times; e-6k times; f-20k times; g-360 times; h-5k times, i-20k times;
[0059] Fig.44 SEM images of the carbon layer of sample 4 at 450°C, a-30 times; b-70 times; c-220 times; d-2.5k times; e-5k times; f-8k times;
[0060] Fig.45 SEM images of the carbon layer of sample 4 at 470°C, a-60 times; b-30 times; c-600 times; d-600 times; e-250 times; f-11k times; g-80k times; h-70k times, i-70k;
[0061] Fig.46SEM images of the carbon layer of sample 4 at 500°C, a-30 times; b-100 times; c-220 times; d-150 times; e-250 times; f-2.2k times; g-350 times; h-8k times, i-40k times; j-9k times; k-25k times; l-35k;
[0062] Fig.47 This is the elemental analysis diagram of the smooth surface of sample 4 calcined at 500°C;
[0063] Fig.48 This is the elemental analysis diagram of the surface of the fragments of sample 4 calcined at 500°C;
[0064] Fig.49 This is the elemental analysis diagram of the surface of the flake of sample 4 calcined at 500°C;
[0065] Fig.50 This is the element analysis diagram of the cylinder surface of sample 4 calcined at 500°C;
[0066] Fig.51 SEM images of the carbon layer of sample 6 at 180°C, a-130 times; b-600 times; c-5k times; d-50k times;
[0067] Fig.52 SEM images of the carbon layer of sample 6 at 190°C, a-100 times; b-300 times; c-2.2k times; d-35k times;
[0068] Fig.53 SEM images of the carbon layer of sample 6 at 200°C, a-150 times; b-300 times; c-5k times; d-30k times;
[0069] Fig.54 SEM images of the carbon layer of sample 6 at 210°C, a-110 times; b-3k times; c-20k times; d-50k times;
[0070] Fig.55 SEM images of the carbon layer of sample 6 at 220°C, a-2k times; b-5k times; c-30k times; d-30k times;
[0071] Fig.56 SEM images of the carbon layer of sample 6 at 230°C, a-250 times; b-800 times; c-1.8k times; d-10k times;
[0072] Fig.57 SEM images of the carbon layer of sample 6 at 240°C, a-200 times; b-5k times; c-22k times; d-70k times;
[0073] Fig.58SEM images of the carbon layer of sample 6 at 250°C, a-300 times; b-2.5k times; c-20k times; d-4k times;
[0074] Fig.59 SEM images of the carbon layer of sample 6 at 260°C, a-450 times; b-700 times; c-1.2k times; d-1.8k times;
[0075] Fig.60 SEM images of the carbon layer of sample 6 at 270°C, a-1.8k times; b-4k times; c-45k times; d-20k times;
[0076] Fig.61 SEM images of the carbon layer of sample 6 at 280°C, a-350 times; b-800 times; c-5k times; d-50k times;
[0077] Fig.62 SEM images of the carbon layer of sample 6 at 290°C, a-300 times; b-2.5k times; c-10k times; d-20k times;
[0078] Fig.63 SEM images of the carbon layer of sample 6 at 300°C, a-350 times; b-10k times; c-50k times; d-110k times;
[0079] Fig.64 SEM images of the carbon layer of sample 6 at 330°C, a-40 times; b-150 times; c-150 times; d-500 times;
[0080] Fig.65 SEM images of the carbon layer of sample 6 at 350°C, a-60 times; b-250 times; c-250 times; d-1.5k times;
[0081] Fig.66 SEM images of the carbon layer of sample 6 at 370°C, a-60 times; b-150 times; c-800 times; d-250 times; e-1k times; f-3k times; g-10k times; h-5k times, i-10k times;
[0082] Fig.67 SEM images of the carbon layer of sample 6 at 400°C, a-220 times; b-3.5k times; c-7k times; d-45 times; e-110 times; f-250 times; g-5k times; h-4.5k times, i-2k times;
[0083] Fig.68SEM images of the carbon layer of sample 6 at 430°C, a-30 times; b-110 times; c-350 times; d-1k times; e-300 times; f-5k times; g-3k times; h-20k times; i-30k times; j-800 times; k-2k times; l-10k times; m-30 times; n-350 times; o-10k times;
[0084] Fig.69 SEM images of the carbon layer of sample 6 at 450°C, a-80 times; b-2k times; c-5k times; d-400 times; e-700 times; f-3k times; g-300 times; h-2.2k times; i-4k times; j-4k times; k-2.5k times; l-10k times;
[0085] Fig.70 SEM images of the carbon layer of sample 6 at 470°C, a-30 times; b-120 times; c-300 times; d-500 times; e-5k times; f-10k times; g-50k times; h-1k times; i-10k times; j-30 times; k-5k times; l-40k times; m-100 times; n-500 times; o-20k times;
[0086] Fig.71 SEM images of the carbon layer of sample 6 at 500°C, a-110 times; b-90 times; c-600 times; d-1k times; e-5k times; f-13k times; g-40k times; h-1.3k times; i-4.5k times;
[0087] Fig.72 SEM images of the carbon layer of sample 8 at 300°C, a-60 times; b-120 times; c-80 times; d-200 times;
[0088] Fig.73 SEM images of the carbon layer of sample 8 at 350°C, a-80 times; b-150 times; c-150 times;
[0089] Fig.74 SEM images of the carbon layer of sample 8 at 400°C, a-45 times; b-100 times; c-250 times; d-1k times; e-3k times; f-1k times;
[0090] Fig.75 SEM images of the carbon layer of sample 8 at 450°C, a-30 times; b-300 times; c-10k times; d-200 times; e-1k times; f-10k times; g-35 times; h-150 times; i-1k times;
[0091] Fig.76SEM images of the carbon layer of sample 8 at 500°C, a-30 times; b-120 times; c-100 times; d-100 times; e-50 times; f-300 times; g-3k times; h-15k times; i-700 times;
[0092] Fig.77 SEM images of the carbon layer of sample 8 at 530°C, a-30 times; b-400 times; c-10k times; d-3.5k times; e-4.5k times; f-12k times;
[0093] Fig.78 is the EDS mapping image of sample 1;
[0094] Fig.79 is the elemental analysis diagram of sample 1;
[0095] Fig.80 This is the 4-element analysis diagram of the sample calcined at 500°C;
[0096] Fig.81 Element analysis diagram of sample 6 calcined at 500°C;
[0097] Fig.82 Element analysis diagram of sample 8 calcined at 500℃;
[0098] Fig.83 The morphology of the carbon layer of sample 6-8 calcined at 500°C;
[0099] Fig.84 Digital photos of the carbon layer of sample 4 calcined at different temperatures;
[0100] Fig.85 These are digital photos of the carbon layer of sample 6 calcined at different temperatures. DETAILED DESCRIPTION
[0101] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0102] Example 1: Preparation of zinc-containing ionic liquid
[0103] Weigh 30.0g acrylamide and 0.03g of p-Hydroxyanisole (0.3% of acrylamide quality) and place in a 250mL round-bottomed flask, after mixing, flask is put into an oil bath, after being heated to 80 ℃ of dissolvings under magnetic agitation condition, add 30.0g zinc chloride again, continue heated and stirred 3h under condensation reflux condition.Add 100mL acetone 60 ℃ of reactions 3h, after reaction finishes, 60 ℃ of rotary vacuum dryings promptly obtain the clear target product, containing zinc ion liquid, be designated as Zn (Am) Cl 2.Pack product into sealed preservation in the sample bottle and be positioned in a cool place for later use.
[0104] Example 2: Preparation and curing method of Zn-containing multi-layer high-efficiency synergistic flame-retardant epoxy acrylic coating
[0105] According to the formula in Table 1, the flame-retardant EA coating containing zinc ion liquid was prepared by light curing method. According to Table 1, the flame-retardant coating was prepared. First, 8 dry and clean small beakers were prepared and labeled respectively. The beakers were peeled and weighed. The order of adding materials was as follows: the formula amount of Zn(Am)Cl2, 5g of epoxy acrylate, and 0.3g of 1173 initiator were stirred evenly, slightly heated and ultrasonically vibrated until the bubbles were eliminated, and stirred into a uniform solution.
[0106] Table 1 Zn(Am)Cl2 / EA flame retardant system formula
[0107]
[0108] Preparation of coating film: First, take a clean and dry glass plate, wipe it with anhydrous ethanol, and label it; then select a 150μm wet film preparation device; drop the sample that has just been ultrasonically vibrated on the glass plate, hold the glass plate with your left hand, and hold the wet film preparation device with your right hand and slide it gently and evenly to obtain a 150μm coating film; finally, put the glass plate under a UV lamp to cure for 20s, take it out for use, and record it as Zn(Am)Cl2 / EA coating.
[0109] In order to understand the composition and structure of each sample, nuclear magnetic resonance, scanning electron microscope (SEM), X-ray diffractometer (XRD), X-ray photoelectron spectrometer, Fourier transform infrared spectrometer (FT-IR), UV / visible spectrophotometer, thermogravimetric analyzer (TG), vertical water combustion tester, HSC-4 thermal analyzer and other instruments were used to characterize the samples.
[0110] Test Example 1: NMR Analysis
[0111] Place the sample into the tubular sample chamber of the NMR instrument, and then start the test through command line operation. Based on the obtained NMR spectrum, qualitative and quantitative analysis can be performed to determine the composition of the sample through the chemical shift of the signal peak and the peak area ratio.
[0112] Figure 1 This is the NMR spectrum of zinc ionic liquid Zn(Am)Cl2. 1 H NMR (500MHz, DMSO-d6) δ7.51 (s, 1H), 7.05 (s, 1H), 6.14 (dd, J = 17.2, 10.0 Hz, 1H), 6.02 (d, J = 17.2 Hz, 1H), 5.56 (d, J = 10.2 Hz, 1H). The analysis results showed that the zinc ion liquid was consistent with the partial structure of acrylamide.
[0113] Test Example 2: Infrared spectroscopy analysis
[0114] The synthetic product and the carbon layer after the coating combustion were analyzed by infrared analysis using a TENSOR 27 Fourier transform infrared spectrometer (FT-IR Spectrometer, FTIR) from Bruker, Germany. The wave number measurement range was set to: 4000-500 cm -1 .
[0115] Different functional groups bend, stretch, and wiggle at different frequencies. If the frequency of light matches the frequency of the stretching, bending, or wiggling of a functional group, that functional group absorbs the light. The infrared spectrum shows absorption bands that can determine if certain functional groups are present in a molecule.
[0116] In infrared spectroscopy, although some chemical groups are in different molecules, their absorption frequencies always appear in a narrow range, with large absorption intensity, and the frequency does not change significantly with changes in molecular configuration. This type of frequency is called group frequency, and its location is generally called characteristic absorption peak.
[0117] The main function of infrared spectroscopy is to show the absorption peaks of various bonds and groups within the molecule, including hydrogen bonds, double bonds, single bonds and specific functional groups (such as CO bonds, NH bonds, CH=CH2 bonds, etc.). In the reaction of acrylamide and ZnCl2, characteristic absorption peaks in the following key areas can be observed.
[0118] Figure 2 This is the infrared spectrum of ZnCl2, AM, and Zn(Am)Cl2. As can be seen from the figure: in the IR spectrum of ZnCl2, 659cm -1 The characteristic absorption peak of Zn-O bond, 525 cm -1 It is the characteristic absorption peak of Zn-Cl bond. In the IR spectrum of AM, 3340cm -1 The absorption peak of NH bond is 3230cm -1 The absorption peak of OH bond is 1673cm -1The absorption peak of C=O is 1613cm -1 and 1425cm -1 The absorption peak of -NC=O bond is at 1613cm -1 The broad peak also corresponds to the characteristic absorption peak of C=C bond, 1279 cm -1 The absorption peak of CC bond is at 978cm -1 The absorption peak of CH=CH2 bond is 833cm -1 The out-of-plane bending vibration of the CH bond is at 1670cm -1 The absorption peak of C=O is 1620cm -1 The absorption peak of C=C bond is 1580cm -1 and 1440cm -1 The absorption peak of -NC=O bond is 1280cm -1 The absorption peak of CC bond is at 978cm -1 The absorption peak of CH=CH2 bond is 808cm -1 The out-of-plane bending vibration of the CH bond is 542 cm -1 Based on the above analysis, the reaction product of acrylamide and ZnCl2 exhibits characteristic absorption peaks of multiple functional groups in the infrared spectrum, including OH bond, CC bond, C=O double bond, -CNO bond, etc., indicating that acrylamide and zinc chloride reacted.
[0119] Figures 3 to 5 This is the infrared test result of thermal degradation of sample 4. From the analysis of the figure, we can see that at 3500cm -1 There is a characteristic absorption peak of NH bond at 2967cm, but there is no obvious characteristic absorption peak at 280℃, which means that it is almost completely degraded at 280℃. -1 There is a characteristic absorption peak of CH bond at 2874cm, but there is no obvious characteristic absorption peak at 400℃, which means that the degradation is basically completed at 400℃. -1 There is a characteristic absorption peak of CH bond at 1723cm, but there is no obvious characteristic absorption peak at 350℃, indicating that it is almost completely degraded at 350℃. -1 There is a characteristic absorption peak of C=O bond at 1657cm, but there is no obvious characteristic absorption peak at 350℃, indicating that it is basically degraded at 350℃. -1 There is an amide C=O bond at 1607cm-1, but there is no obvious characteristic absorption peak at 230℃, indicating that it is completely degraded at 230℃. -1There is a characteristic absorption peak of C=C bond at 1509cm-1, which decreases significantly at 350℃, indicating that a significant structural transformation occurs at 350℃, which may be caused by the significant presence of carbon layer composed of polycyclic aromatic compounds generated by the flame retardant promoting the degradation of polymer. -1 There is a characteristic absorption peak of -CNO bond at 1291cm-1, but there is no obvious characteristic absorption peak at 350℃, indicating that it is almost completely degraded at 350℃. -1 There is a characteristic absorption peak of ester group at 1178cm, but there is no obvious characteristic absorption peak at 230℃, which indicates that it is almost completely degraded at 230℃. -1 There is also a characteristic absorption peak of the ester group at 1039 cm-1, but there is no obvious characteristic absorption peak at 350 °C, indicating that the degradation is basically complete at 350 °C. -1 There is a characteristic absorption peak of CO bond at 826 cm-1, but there is no obvious characteristic absorption peak at 350 °C, indicating that it is completely degraded at 350 °C. -1 There is a characteristic absorption peak of the para-CH bond of the aromatic ring at 554 cm-1, but there is no obvious characteristic absorption peak at 350 °C, which means that the degradation is almost complete at 350 °C. -1 There is a characteristic absorption peak of Zn-Cl bond at 350℃, but there is no obvious characteristic absorption peak at 350℃, which means that it is completely degraded at 350℃. It also indicates that there is a morphological change of Zn element at this time, which may be related to the structure of another substance generated during the catalytic carbonization process.
[0120] Figures 6 to 8 The infrared test results of thermal degradation of sample 6 are shown in Figure 3. -1 There is a characteristic absorption peak of NH bond at 2967cm, but there is no obvious characteristic absorption peak at 350℃, which means that it is completely degraded at 350℃. -1 There is a characteristic absorption peak of CH bond at 2874cm, but there is no obvious characteristic absorption peak at 400℃, which means that it is almost completely degraded at 400℃. -1 There is a characteristic absorption peak of CH bond at 1723 cm-1, but there is no obvious characteristic absorption peak at 350 °C, which means that it is almost completely degraded at 350 °C. -1 There is a characteristic absorption peak of C=O bond at 1657cm, but there is no obvious characteristic absorption peak at 350℃, which means that it is basically degraded at 350℃. -1 There is an amide C=O bond at 1607cm-1, and there is no obvious characteristic absorption peak at 290℃, which means that it is completely degraded at 290℃. -1There is a characteristic absorption peak of C=C bond at 1509cm. At 400℃, the characteristic absorption peak here becomes gentle, which indicates that the coating structure morphology has undergone a significant change at 400℃, which may be due to the further formation of the condensed aromatic structure of the carbon layer. -1 There is a characteristic absorption peak of -CNO bond at 1291cm, but there is no obvious characteristic absorption peak at 400℃, which means that it is almost completely degraded at 400℃. -1 There is a characteristic absorption peak of ester group at 1178cm, but there is no obvious characteristic absorption peak at 350℃, which means that it has been basically degraded at 350℃. -1 There is a characteristic absorption peak of ester group at 1039cm-1, but there is no obvious characteristic absorption peak at 350℃, which means that it is almost completely degraded at 350℃. -1 There is a characteristic absorption peak of CO bond at 826 cm-1, but there is no obvious characteristic absorption peak at 350 °C, which means that it is almost completely degraded at 350 °C. -1 There is a characteristic absorption peak of the para-CH bond of the aromatic ring at 554 cm-1. However, there is no obvious characteristic absorption peak at 350 °C, which means that the degradation is almost complete at 350 °C. -1 There is a characteristic absorption peak of Zn-Cl bond at 350℃, but there is no obvious characteristic absorption peak at 350℃, which means that it has been basically degraded at 350℃. It may be caused by the structural morphology transformation when Zn ions participate in the catalytic carbonization of polymer, which will be further revealed in the microstructural analysis of the prepared flame retardant coating below.
[0121] In summary, the real-time infrared analysis results of sample 4 containing 30% zinc ionic liquid and sample 6 containing 50% zinc ionic liquid are consistent, and the degradation rules of the groups are basically the same. -1 There is a characteristic absorption peak of NH bond at 1657cm -1 There is an amide C=O bond at 1607cm. Sample 4 is almost completely degraded at 230℃, while sample 6 is completely degraded at 290℃. -1 There is a characteristic absorption peak of C=C bond at 1509cm -1 There is a characteristic absorption peak of -CNO bond at 1291cm -1 There is a characteristic absorption peak of ester group at , sample 4 is completely degraded at 230℃, while sample 6 is completely degraded at 350℃. This shows that the higher the content of zinc-containing ionic liquid, the slower the degradation of organic groups in the coating and the better the thermal degradation stability of the coating.
[0122] It can be seen that the absorption peak of Zn(Am)Cl2 / EA flame retardant coating is basically unchanged before 280℃, and its thermal stability is good. As the temperature increases, the corresponding absorption peak intensity begins to decrease, and it is completely degraded after 350℃, leaving only the carbon layer. At the same time, from the comparison of sample 4 and sample 6, it can be seen that the degradation temperature of some absorption peaks of sample 6 is higher than that of sample 4, indicating that the increase in the content of zinc ionic liquid can improve its thermal stability.
[0123] Experimental Example 3: X-ray diffraction pattern analysis
[0124] The XRD-6100 X-ray diffractometer was used to continuously scan the carbon layer after calcination at 500°C. The scanning range was 0° to 80° and the scanning rate was 2° / min. The diffraction pattern was analyzed to study the composition of the material and the structural morphology of atoms or molecules inside the material.
[0125] X-ray diffraction (XRD) is the main method for studying the phase and crystal structure of a substance. When a substance (crystalline or amorphous) is subjected to diffraction analysis, the substance is irradiated with X-rays to produce different degrees of diffraction. The material properties such as the composition, crystal form, intramolecular bonding mode, molecular configuration, conformation, etc. determine the unique diffraction pattern produced by the substance.
[0126] Fig. 9 This is the X-ray diffraction pattern of the carbon layer of sample 6-8 coating calcined at 500℃. Fig.10 The X-ray diffraction diagram of nano ZnO shows that although the zinc ion content is different, the substances produced by the degradation of the coating at the same temperature are the same, and the diffraction peaks of the newly generated substances are clearly visible. At the same time, it can be found that the diffraction peaks of the newly generated substances in the range of 30-80° are the same as those in the Fig.10 The diffraction peaks of nano ZnO are consistent, which indicates that Zn(Am)Cl2 is calcined and thermally decomposed to generate ZnO, that is, it is oxidized to generate metal compounds, which is consistent with the SEM analysis results of the calcined carbon layer of the flame retardant coating below; moreover, it can be found from the figure that a characteristic diffraction peak similar to graphene oxide appears at 11.2°, which shows that the carbon element in the residual carbon structure of the flame retardant EA coating containing zinc ion liquid has a more complex form, which may be a mixture of graphene oxide, graphite oxide and graphite.
[0127] Test Example 4: Thermogravimetric Analysis
[0128] The thermal degradation process of the coating was analyzed using an SDT650 thermogravimetric analyzer. First, 12 to 20 mg of a regular block sample was taken and placed in a constant temperature drying oven for 6 hours, with the temperature set to 70°C. The sample was then analyzed using a thermogravimetric analyzer, with the temperature set to 30 to 800°C, the air flow rate to 30°C / min, and the heating rate to 10°C / min. According to the TG curve and the DTG curve, the mass change information of the coating at different temperatures can be obtained, and then its pyrolysis behavior and its effect on flame retardant properties can be analyzed.
[0129] Thermogravimetric analysis is to place the sample under a certain temperature program (heating or constant temperature) to observe how the sample's mass changes with temperature or time, and obtain relevant information such as weight loss temperature (starting point, peak value, end point, etc.), weight loss, and decomposition residue.
[0130] The larger the mass, the higher the decomposition temperature and the longer the decomposition process, generally 3-5mg. The faster the heating rate, the higher the decomposition temperature, generally 5K / min or 10K / min. The larger the sample particles, the higher the decomposition temperature and the longer the decomposition process, generally powder is used for testing. For mixtures with complex components and different decomposition temperatures of different components, multiple weight loss steps will appear. TGA technology is particularly important for the analysis of flame retardant properties of coatings. By analyzing the TG and DTG curves of coating samples at different temperatures and times, the thermal decomposition process and flame retardant mechanism of the coating can be revealed.
[0131] Fig.11 The TG curve of sample 1-8 coating reflects the relationship between the coating mass and temperature under program temperature control. From the analysis of the figure, it can be seen that the thermal decomposition of sample 1 is divided into three stages. 100-341℃ is the first stage. In this stage, the weight loss of the coating is very small, indicating that the coating has not yet degraded in this stage. The small amount of mass loss may be caused by the loss of water in the coating; 341-400℃ is the second stage. In this stage, the weight loss of the coating is very large and obvious. This is the first decomposition temperature interval of the coating. It means that in this stage, the coating is rapidly degraded under the action of high temperature, generating water and carbon dioxide, thereby increasing the rate of mass loss of the coating; 400-500℃ is the third stage. In this stage, the weight loss of the coating is also very large. This is the second decomposition temperature interval of the coating. It means that in this stage, the coating is subjected to high temperature, and its carbon layer undergoes oxidative decomposition at high temperature. It can be roughly inferred that the fastest degradation temperature in the first decomposition temperature interval of sample 1 is 341℃, and the fastest degradation temperature in the second decomposition temperature interval is 400℃.
[0132] Through comparative analysis of the 8 samples, it can be seen that the high temperature resistance of sample 1 and sample 2 is weaker, but their thermal weight loss in a lower temperature environment is smaller; the high temperature resistance of sample 8 is stronger, but its thermal weight loss in a lower temperature environment is larger. At the same time, it can be found by comparison that the thermal weight loss in a lower temperature environment (100-341°C) is from high to low: sample 8> sample 7> sample 6> sample 5> sample 4> sample 3> sample 2> sample 1, and the thermal weight loss in a higher temperature environment (341-500°C) is from high to low: sample 1> sample 2> sample 3> sample 4> sample 5> sample 6> sample 7> sample 8. At the same time, since sample 1 is the TG curve of 100% EA coating, compared with the TG curves of the other 7 groups of samples, it can be found that the degradation rate of the coating containing Zn ionic liquid is faster in a lower temperature environment, and the higher the content of Zn ionic liquid, the faster the degradation rate of the corresponding coating in a lower temperature environment; while in a higher temperature environment, the degradation rate of the coating containing Zn ionic liquid is slower than that of the coating not containing Zn ionic liquid, and the higher the content of Zn ionic liquid, the slower the degradation rate of the corresponding coating in a higher temperature environment. This is because under low temperature conditions, the Zn ionic liquid catalyzes the degradation of the polymer. Combined with the scanning electron microscope image of the flame retardant coating, it can be observed that a dense carbon layer with a honeycomb structure is formed on the surface of the coating, and this carbon layer can effectively protect the internal polymer, thereby slowing down its degradation rate under high temperature conditions. In summary, the Zn ionic liquid plays a good flame retardant role in the coating system. It accelerates the carbonization process of the organic matter in the EA coating, thereby achieving the purpose of protecting the coated substrate from degradation.
[0133] Test Example 5: Scanning electron microscope analysis
[0134] The morphology of the samples and coatings was characterized by a SU 8010 scanning electron microscope (SEM) from Hitachi High-Technologies Corporation, and the presence and content of elements were tested by an element analyzer. The carbon layer of the coating after calcination at different temperatures was scanned by a scanning electron microscope, with an acceleration voltage of 10KV and a thickness of 2-3mm for the inner surface slice of the sample. The sample was placed on a tray and electroplated using an electroplating instrument. The electroplated sample was then subjected to a scanning electron microscope to observe the microstructure of the outer surface and inner section of the carbon layer of the coating after high-temperature calcination.
[0135] A scanning electron microscope (SEM) is an electron microscope that uses a high-energy focused electron beam to scan samples to obtain information about the samples. Using an electron beam as the illumination source, applying the principle of electron optics, and using the information generated by the interaction between electrons and matter to form an image, the electron beam scans the surface of the sample. The main features of a scanning electron microscope are: large image depth of field, strong three-dimensional sense; high resolution; simple sample preparation; direct observation of large-sized samples; large field of view; low contamination of the sample surface; large degree of freedom of the sample in the sample chamber; large magnification, from several times to hundreds of thousands times; and the ability to conduct many in-situ experiments.
[0136] Fig.12 The electron microscope images of the outer surface and inner section of the carbon layer of sample 1 calcined in a muffle furnace at 300°C. Sample 1 is a 100% EA coating. From the electron microscope images of the carbon layer, it can be seen that the outer surface of the 100% EA coating is smooth, and the section is wrinkled; Fig.13 The electron microscope images of the outer surface and inner section of the carbon layer of sample 1 calcined in a muffle furnace at 350°C. From the electron microscope images of the carbon layer above, it can be seen that: the outer surface of the 100% EA coating has clear layers, and the section is more wrinkled; Fig.14 The electron microscope images of the outer surface and inner section of the carbon layer of sample 1 calcined in a muffle furnace at 400°C. From the electron microscope images of the carbon layer above, it can be seen that the outer surface of the 100% EA coating is uneven, the section is very wrinkled, and there are pores of different sizes; Fig.15 The electron microscope images of the outer surface and inner section of the carbon layer of sample 1 calcined in a muffle furnace at 450°C. From the electron microscope images of the carbon layer above, it can be seen that the outer surface of the 100% EA coating has clear layers, and the wrinkled section has pores of different sizes and irregular gaps; Fig.16 The electron microscope images of the outer surface and inner section of the carbon layer of sample 1 calcined in a muffle furnace at 500°C. From the electron microscope images of the carbon layer, it can be seen that the outer surface of the 100% EA coating is rough, and the section has pores of different sizes and irregular gaps.
[0137] From the above electron microscope images of the carbon layer, it can be seen that as the temperature increases, the surface of the 100% EA coating gradually becomes rough and wrinkled, and no independent air chamber is generated, that is, the coating does not expand when heated, indicating that the 100% EA coating does not form an expanded carbon layer during the combustion process.
[0138] Figures 17 to 19 The electron microscope images of the outer surface and inner section of the carbon layer of Sample 2 calcined in a muffle furnace at 300°C, 330°C and 350°C respectively. Sample 2 is an EA coating containing 10% zinc ion liquid. It can be seen from the above electron microscope images of the carbon layer that: as the temperature increases, the surface changes from rough and wrinkled to smooth, and it can be seen that the pores increase and become larger.
[0139] Fig. 20The electron microscope images of the outer surface and inner section of the carbon layer of sample 2 calcined in a muffle furnace at 370°C. From the electron microscope images of the carbon layer above, it can be seen that the coating expands due to heat, and the air film is wrapped between the chambers. Some of the air films bulge, and some of the air films collapse. The cross section is honeycomb-shaped. Possibly due to uneven concentration distribution, geometric flakes appear on the surface.
[0140] Figure 21 to Figure 25 The electron microscope images of the outer surface and inner section of the carbon layer of sample 2 calcined in a muffle furnace at 400℃, 430℃, 450℃, 470℃, and 500℃ respectively. From the electron microscope images of the carbon layer, it can be seen that the coating is carbonized, and some gas films have been broken by the CO2 and other gases produced by the degradation of the polymer, and the carbon layer has also become brittle. With the increase of temperature, when the temperature reaches 470℃, most of the gas films no longer exist, and some pores collapse due to the embrittlement of the carbon layer, becoming larger holes.
[0141] Fig.26 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 190°C. Sample 4 is an EA coating containing 30% zinc ion liquid. From the above electron microscope images of the carbon layer, it can be seen that the outer surface of the carbon layer of the EA coating containing 30% zinc ion liquid is smooth and distinct, and the cross-section of the carbon layer is wrinkled and rough and has irregular pores.
[0142] Fig. 27 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 190°C. From the electron microscope images of the carbon layer above, it can be seen that the carbon layer is basically unchanged compared with the carbon layer at 190°C.
[0143] Fig.28 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 200°C show that the outer surface of the carbon layer is smooth, the cross section of the carbon layer is increasingly wrinkled and uneven, and the surface has irregular pores.
[0144] Fig.29 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 210°C show that the outer surface of the carbon layer is rough, and the cross-section of the carbon layer has more and more pores and is uneven.
[0145] Fig.30 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 220°C show that the outer surface of the carbon layer becomes rougher and irregular patterns appear on the wrinkled surface of the carbon layer section.
[0146] Fig.31 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 230°C show that the outer surface of the carbon layer is rough and uneven, and the cross-sectional wrinkles of the carbon layer are densely covered with irregular patterns.
[0147] Figure 31 to Figure 36 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 230℃, 240℃, 250℃, 260℃, 270℃, and 280℃ respectively. It can be seen from the electron microscope images of the carbon layer that as the temperature increases, the outer surface of the carbon layer becomes rougher, the wrinkled surface of the carbon layer section is densely covered with irregular patterns and uneven, and the irregular pores are also increasing and increasing. This is because as the temperature increases, the flame retardant gradually reaches the initial temperature of catalytic polymer degradation, and the interface with a large contact surface shows signs of degradation, forming a viscous substance similar to molten slurry. When it is taken out of the muffle furnace at a certain temperature, shrinkage wrinkles will occur, and even the gas generated by the flame retardant catalysis will move in the molten slurry to produce obvious protrusions and irregular concave-convex surface structures. This phenomenon will be aggravated especially when the molten slurry encounters sudden cooling. However, the gas source at this time has not yet been decomposed in large quantities, so the expansion structure caused by the gas has not yet formed.
[0148] Fig.37 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 290°C. From the electron microscope images of the carbon layer, it can be seen that the outer surface of the carbon layer tends to be smooth, the cross section of the carbon layer is rough, and the surface particles are uneven. The carbon layer of the sample at this temperature has a significant protrusion structure, which may be caused by the increased movement of gas generation.
[0149] Fig.38 and Fig.39 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 300℃ and 330℃ respectively. From the electron microscope images of the carbon layer, it can be seen that the outer surface of the carbon layer is smooth and clearly layered, the cross section of the carbon layer is wrinkled and uneven, and the irregular pores are significantly increased. This is because the temperature is further increased, the catalytic degradation is intensified, the internal stress of the carbon layer is significantly enhanced, and the continuously decomposed gas also intensifies the rupture of a few previously generated pores, resulting in a significant increase in irregular pores.
[0150] From the above electron microscope images of the carbon layer, it can be seen that as the temperature of the EA coating containing 30% zinc ionic liquid increases, the cross-section of the carbon layer becomes increasingly irregular and gradually becomes smooth, forming an air film, and then the number of air chambers gradually increases, and the diameter of the pores gradually increases.
[0151] Fig.40 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 350°C show that the coating expands due to heat, forming many independent air chambers of different sizes inside, with a honeycomb-shaped section, and the chambers are wrapped with expanding air films.
[0152] Fig.41The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 370°C show that the diameter of the air chamber inside the carbon layer increases, the air films are wrapped between the chambers, the volume of the air films increases, and some air films are broken.
[0153] Fig.42 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 400°C show that the gas chambers formed inside the carbon layer are enlarged and increased, and the gas film is broken more seriously.
[0154] Fig.43 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 430°C. From the electron microscope images of the carbon layer above, it can be seen that the greater the carbon layer expands due to heat, the more serious the air chamber breaks, the air film collapses, and many triangular and hexagonal flakes of different sizes appear around these air films. A large number of hexagonal prisms with regular shapes appear on the outer surface, close to each other. When magnified to 20K times, according to its scale, it can be roughly inferred that the height of the hexagonal prism is 2μm and the length of the base is 500nm.
[0155] Fig.44 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 450°C show that the carbon layer expands due to heat, the broken air chamber presents a honeycomb shape, the air film expands to collapse, and the number of triangular and hexagonal flakes around it increases.
[0156] Fig.45 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 470°C. From the electron microscope images of the carbon layer, it can be seen that the carbon layer further expands due to heat, the air film collapses severely, the air chamber is severely broken, and the whole is honeycomb-shaped. A large number of lotus-shaped columns composed of hexagonal sheets appear on the outer surface in clusters.
[0157] Fig.46 The electron microscope images of the outer surface and inner section of the carbon layer of sample 4 calcined in a muffle furnace at 500°C show that the gas chamber is severely broken, a large number of geometric bodies of different sizes appear on the surface of the carbon layer skeleton, and a large number of regular crystals evolved from hexagonal prisms appear on the outer surface, stacked together.
[0158] From the electron microscope image of the carbon layer, it can be seen that the coating expands as the temperature continues to rise to 350°C, and gas films of varying sizes appear inside it. When the temperature rises to 400°C, the coating continues to decompose due to heat, and the CO2 and other gases produced continue to increase, causing the gas chamber to expand and rupture. At 430°C, regular hexagonal prism crystals appear on the outer surface of the coating, and many scattered triangular and hexagonal flakes appear on the surface. As the temperature rises, the flakes stack into hexagonal prisms. When the temperature rises to 500°C, the hexagonal prism crystals become cone-shaped crystals.
[0159] Fig.47 This is the elemental analysis diagram of the smooth surface of sample 4 calcined at 500°C. Fig.48 This is the surface element analysis diagram of the fragments of sample 4 calcined at 500℃. Fig.49 This is the elemental analysis diagram of the surface of the sample 4 containing thin slices calcined at 500℃. Fig.50 The element analysis diagram of the surface of the column of sample 4 calcined at 500°C is shown in Table 2.
[0160] Table 2 shows the elemental analysis data of different surfaces of sample 4
[0161]
[0162] Depend on Figures 47 to 50 As can be seen from Table 4, the different surfaces of sample 4 produced after calcination at 500°C are composed of five elements: C, N, O, Zn, and Cl. The nearly smooth surface contains the most C and the least Zn. The surface of scattered fragments contains an increased Zn content, and the surface of dense flakes contains a further increased Zn content. The surface of dense columns contains the most Zn, followed by O, and the least C. It can be roughly inferred that the main component of the geometric fragments, flakes, and columns appearing on the surface is Zn.
[0163] Combining the previous XRD analysis results and energy spectrum research, and comparing with the relevant literature on the preparation and structural analysis of nano-ZnO, we know that the main components of the flame retardant coating are Zn geometric fragments, flakes and columns, which are nano-ZnO with different crystalline structures.
[0164] In summary, the flame retardant structure microscopic study shows that the Zn(Am)Cl2 / EA coating prepared in the embodiment can produce nano ZnO when flame retardant, and participate in the construction of nano flame retardant carbon layer, and play a synergistic flame retardant role with its own expansion flame retardant carbon layer, so that the low temperature part is mainly expansion flame retardant, and the high temperature part is mainly nano flame retardant, and is also supplemented by expansion flame retardant, thus forming a layered flame retardant, which is also helpful to form a high-efficiency flame retardant EA coating, which is consistent with the flame retardant performance test results later. The study of the microscopic carbonization process of the flame retardant coating reveals the carbonization law of the flame retardant catalytic coating, and provides a theoretical basis for the preparation of high-efficiency flame retardant coatings.
[0165] Fig.51 The electron microscope images of the outer surface and inner section of the carbon layer of sample 6 calcined in a muffle furnace at 180°C. Sample 6 is an EA coating containing 50% zinc ion liquid. From the above electron microscope images of the carbon layer, it can be seen that: the outer surface of the carbon layer is smooth, the cross-section of the carbon layer has wrinkles, uneven layers, and irregular pores are more obvious than those of the aforementioned samples.
[0166] Figure 52 to Figure 55The electron microscope images of the outer surface and inner section of the carbon layer of sample 6 calcined in a muffle furnace at 190℃, 200℃, 210℃, and 220℃ are shown. From the electron microscope images of the carbon layer, it can be seen that the outer surface of the carbon layer gradually becomes rough from smooth, the cross section of the carbon layer becomes more wrinkled, the layers are uneven, the irregular pores increase, and the surface gradually becomes uneven.
[0167] Fig.56 The electron microscope images of the outer surface and inner section of the carbon layer of sample 6 calcined in a muffle furnace at 230°C show that the outer surface of the carbon layer tends to be smooth, the cross section of the carbon layer is still wrinkled, and the irregular pores are further enlarged.
[0168] Fig.57 The electron microscope images of the outer surface and inner section of the carbon layer of sample 6 calcined in a muffle furnace at 240°C show that the outer surface of the carbon layer is smooth and flat, the cross section of the carbon layer is wrinkled, the number of irregular pores increases, and the outer surface is covered with irregular patterns.
[0169] Fig.58 The electron microscope images of the outer surface and inner section of the carbon layer of sample 6 calcined in a muffle furnace at 250°C. From the electron microscope images of the carbon layer, it can be seen that the outer surface of the carbon layer is still smooth and flat, and the irregular pattern of the cross section of the carbon layer gradually bulges.
[0170] Figure 59 to Figure 63 The electron microscope images of the outer surface and inner section of the carbon layer of sample 6 calcined in a muffle furnace at 260℃, 270℃, 280℃, 290℃ and 300℃ respectively. From the electron microscope images of the carbon layer, it can be seen that the outer surface of the carbon layer changes from rough to smooth, the cross section of the carbon layer becomes more wrinkled, the number of irregular pores increases and becomes larger, the layers are clear, and the number of surface pores also increases.
[0171] It can be seen from the above electron microscope images of the carbon layer that as the temperature of the EA coating containing 50% zinc ionic liquid increases, the cross-section of the carbon layer becomes more and more irregular. At 270°C, the cross-section of the carbon layer becomes smooth and an air film is formed. Then, the number of air chambers gradually increases, and the diameter of the pores gradually increases.
[0172] Fig.64 The electron microscope images of the outer surface and inner section of the carbon layer of sample 6 calcined in a muffle furnace at 330°C show that the carbon layer expands due to heat, forming many independent air chambers of different sizes inside, with air films between the chambers.
[0173] Fig.65 The electron microscope images of the outer surface and inner section of the carbon layer of sample 6 calcined in a muffle furnace at 350°C. From the electron microscope images of the carbon layer, it can be seen that the carbon layer expands due to heat, and the section shows many independent air chambers of different sizes formed inside it, showing a honeycomb shape. The individual air films wrapped between the chambers are broken, and many spots are found on its surface.
[0174] Fig.66 The electron microscope images of the outer surface and inner section of the carbon layer of sample 6 calcined in a muffle furnace at 370°C. From the electron microscope images of the carbon layer, it can be seen that the carbon layer further expands due to heat, the diameter of the air chamber increases, the volume of the air film increases, and a large number of broken air films exist on the surface of the carbon layer. It can be seen that the air film is broken into needle-shaped fragments and accumulates in large quantities.
[0175] Fig.67 The electron microscope images of the outer surface and inner section of the carbon layer of sample 6 calcined in a muffle furnace at 400°C show that the carbon layer expands more and more, the air chamber gradually breaks, the air film collapses, and the section presents a uniform and compact honeycomb shape. There are broken air films on the surface of the carbon layer, which are broken into needle-shaped fragments and accumulated in large quantities.
[0176] Fig.68 The electron microscope images of the outer surface and inner section of the carbon layer of sample 6 calcined in a muffle furnace at 430°C. From the electron microscope images of the carbon layer, it can be seen that the carbon layer expands due to heat, the air chamber is severely broken, the air film is severely collapsed, the section is honeycomb-shaped, and the surface of the carbon layer skeleton is densely covered with broken air films. It can be seen that the air film is broken into needle-shaped fragments and accumulated around the air film. On the outer surface of the carbon layer, a large number of hexagonal prisms composed of thin sheets are accumulated.
[0177] Fig.69 The electron microscope images of the outer surface and inner section of the carbon layer of sample 6 calcined in a muffle furnace at 450°C. From the electron microscope images of the carbon layer, it can be seen that the carbon layer is expanded and broken, and the internal air chambers are superimposed and broken. There are a large number of air films of different sizes on the carbon layer skeleton. The volume of the air film increases until it collapses and is severely ruptured. There are many protrusions on the surface of the broken air film. At the same time, it is found that the air film is broken into regular hexagons, and a large number of fragments are accumulated on the outer surface.
[0178] Fig.70 The electron microscope images of the outer surface and inner section of the carbon layer of sample 6 containing 50% of carbon calcined in a muffle furnace at 470°C. From the electron microscope images of the carbon layer, it can be seen that the coating expands due to heat, the air chamber is severely broken, only the carbon layer skeleton remains, the air film collapses, and the section presents a honeycomb shape. The carbon layer skeleton is densely covered with triangular and hexagonal flakes, and a large number of needle-shaped flakes are accumulated. On the surface of the carbon layer, a large number of cone-shaped columns are accumulated, and many irregular lines are densely covered.
[0179] Fig.71 The electron microscope images of the outer surface and inner section of the carbon layer of sample 6 calcined in a muffle furnace at 500°C. From the electron microscope images of the carbon layer, it can be seen that the coating expands due to heat, forming many independent air chambers of different sizes, with a large number of air films wrapped between the chambers, the air films are broken, and the cross-section is honeycomb-shaped. A small number of geometric thin layers are distributed on the carbon layer skeleton, and a large number of regular hexagonal prisms are accumulated on the surface of the carbon layer. At the same time, many irregular flakes are scattered around the air chambers.
[0180] From the electron microscope image of the carbon layer, it can be seen that the coating expands with the continuous increase of temperature. When the temperature rises to 370℃, the coating continues to decompose due to heat, and the CO2 and other gases produced continue to increase, causing the air chamber to expand and rupture. At 430℃, the air chamber expands and ruptures, scattering into needle-shaped fragments, accumulating around the air chamber. As the temperature rises, the needle-shaped fragments accumulate and combine into triangular and hexagonal flakes, and the flakes are stacked into columns. As the temperature gradually rises, the columnar surface becomes smooth, forming a regular hexagonal prism.
[0181] Fig.72 The electron microscope images of the outer surface and inner section of the carbon layer of Sample 8 calcined in a muffle furnace at 300°C. Sample 8 is an EA coating containing 70% zinc ion liquid. From the above electron microscope images of the carbon layer, it can be seen that the coating expands due to heat, and many independent air chambers of different sizes are formed inside. There are air films wrapped between the chambers, and the air films are expanded relatively intact.
[0182] Fig.73 The electron microscope images of the outer surface and inner section of the carbon layer of sample 8 calcined in a muffle furnace at 350°C. From the electron microscope images of the carbon layer, it can be seen that the coating further expands when heated, the number of air chambers increases, the diameter increases, and the volume of the air film increases.
[0183] Fig.74 The electron microscope images of the outer surface and inner section of the carbon layer of sample 8 calcined in a muffle furnace at 400°C. From the electron microscope images of the carbon layer, it can be seen that the coating expands due to heat, the air chamber of the section is broken, a large amount of air film collapses, the carbon layer skeleton is densely covered with air film, many fragments are broken and scattered, and there is a geometric film on the surface.
[0184] Fig.75 The electron microscope images of the outer surface and inner section of the carbon layer of sample 8 calcined in a muffle furnace at 450°C. From the electron microscope images of the carbon layer, it can be seen that the coating expands due to heat, the number of air chambers increases, a large number of air films collapse, and the cross section presents a uniform and dense honeycomb shape. The air films densely distributed on the carbon layer skeleton collapse and break, and many fragments are scattered. At the same time, there are a large number of geometric flakes on the surface, and the surface of the carbon layer is densely covered with angular columns stacked by flakes.
[0185] Fig.76 The electron microscope images of the outer surface and inner section of the carbon layer of sample 8 calcined in a muffle furnace at 500°C. From the electron microscope images of the carbon layer, it can be seen that a large number of air chambers inside the carbon layer are broken, the air film collapses, the cross section of the carbon layer presents a uniform and compact honeycomb shape, the carbon layer skeleton is densely covered with collapsed air films, and many fragments are scattered. The surface of the carbon layer is densely covered with regular hexagonal prisms stacked by thin sheets, and the hexagonal prisms are clustered into cauliflower shapes.
[0186] From the electron microscope image of the carbon layer, it can be seen that the coating expands with the continuous increase of temperature. As the coating is continuously decomposed by heat, the CO2 and other gases generated continue to increase, causing the gas film to expand and rupture, scattering into needle-shaped fragments, and accumulating on the carbon layer skeleton. As the temperature further increases, the needle-shaped fragments accumulate and combine into triangular and hexagonal flakes, and the flakes are stacked into columns. As the temperature gradually increases, the columnar surface approaches smoothness, forming a regular hexagonal prism.
[0187] By comparing the SEM images of the carbon layers of Sample 2, Sample 4, Sample 6, and Sample 8 at the same temperature, it can be found that Sample 2 carbonizes at 370°C, Sample 4 expands at 350°C, Sample 6 expands at 330°C, and Sample 8 expands at 300°C. This shows that the increase of zinc-containing ionic liquid can promote the carbonization of the coating, thereby improving its flame retardant properties.
[0188] Fig.77 The electron microscope images of the outer surface and inner section of the carbon layer of sample 8 calcined in a muffle furnace at 530°C. From the electron microscope images of the carbon layer, it can be seen that the carbon layer is embrittled, almost all the air films no longer exist, some pores collapse due to the embrittlement of the carbon layer, and become larger holes, the carbon layer skeleton cracks, and the stacked columns are defective and incomplete, which may be related to the temperature and time.
[0189] Test Example 6: Flame retardant performance analysis
[0190] Mechanical properties measurement: The hardness of the paint film is measured using a QHQ film coating pencil scratch hardness tester. First, fix the standard glass plate coated with the paint film, then install the pencil as required and make it at a 45° angle to the paint film, and measure the hardness of the paint film at a rate of 1 mm·s -1 Shake the spiral rod at a speed of , draw five parallel lines on the surface of the coating film. If there is no trace after wiping with an eraser, the hardness of the pencil at this time is the hardness of the paint film.
[0191] Limiting oxygen index (LOI) was determined using ASTM D2863-77 on a HC-2 oxygen index tester. The sample size was 100×6×3mm. 3 . The sample was placed in an N2 and O2 experimental environment for testing, and the coating burned vertically at the top. LOI refers to the concentration of the volume fraction of oxygen that can just support the combustion of the polymer in a mixed gas environment of oxygen and nitrogen. It is an important index to characterize the combustion behavior of the material. It is generally believed that when the LOI is 22, the substance can burn in the air. A high LOI means that the material is not easy to burn, and a low LOI means that the material is easy to burn. It is generally believed that LOI <22 is a flammable material, LOI between 22 and 27 is a combustible material, and LOI>27 is a flame retardant material.
[0192] Vertical combustion (UL-94) test: Use UL-94 vertical combustion tester to test the combustion level of coating. Test method: After igniting the sample, remove the flame and observe whether the sample is extinguished immediately and no burning body falls off. UL94V0: The sample is extinguished within 30 seconds and no burning body falls off; UL94V1: The sample is extinguished within 60 seconds and no burning body falls off; UL94V2: The sample is extinguished within 60 seconds and burning body falls off.
[0193] Samples 1 to 8 were tested, and the test results are shown in Table 3:
[0194] Table 3 Limiting oxygen index and vertical burning results of UV-cured EA coatings
[0195]
[0196] Samples 1 to 8 are Zn(Am)Cl2 / EA flame retardant systems. Table 5 shows that only sample 1 has a LOI less than 22, sample 2 has a LOI between 22 and 27, and samples 3 to 8 have a LOI above 27, with the highest being sample 8, which reaches 47. Only sample 1 has a vertical combustion level lower than V-2, sample 2 is V-2, and the other vertical combustion levels all reach V-0. Sample 1 is a 100% EA coating, with no Zn(Am)Cl2 in the system, and the content of Zn(Am)Cl2 in the sample 2 system is only 15%. This shows that Zn(Am)Cl2 has a good flame retardant effect, and the LOI reaches 29 when its content in the system reaches 20%. From the appearance properties, it can be seen that when the content of Zn(Am)Cl2 in the system reaches 50%, the coating changes from colorless and transparent to light yellow and transparent, and when the content of Zn(Am)Cl2 ionic liquid continues to increase, the color of the coating will deepen. In terms of hardness, the flame retardant coatings of this system all reach 5H, and some reach 6H.
[0197] Test Example 7: EDS Analysis
[0198] Fig.78 is the EDS mapping of sample 1, Fig.79 This is the element analysis diagram of sample 1, and the elements of sample 1 are analyzed, as shown in Table 4.
[0199] Table 4 Elemental analysis data of sample 1
[0200]
[0201] from Fig.78 , Fig.79 As can be seen from Table 6, sample 1 is a 100% EA coating, and after calcination at 300°C, its carbon layer is composed of three elements: C, N, and O.
[0202] Fig.80This is the 4-element analysis diagram of the sample calcined at 500℃. Fig.81 6 element analysis diagram of the sample calcined at 500℃, Fig.82 The element analysis diagram of sample 8 calcined at 500°C, and the elements of sample 4, sample 6 and sample 8 were analyzed, as shown in Table 5.
[0203] Table 5 Elemental analysis data of each sample
[0204]
[0205]
[0206] from Figure 80 to Figure 82 As can be seen from Table 7, after calcination at 500℃, the densely distributed hexagonal prisms on the surface of the Zn(Am)Cl2 / EA coating are composed of five elements: C, N, O, Zn, and Cl, with the highest content of Zn and the second highest content of O. At the same time, XRD analysis shows that there is ZnO in the carbon layer. According to the literature, ZnO has a variety of different morphologies, such as lotus-shaped twin crystals, spherulite crystals composed of hexagonal columns, spherulite crystals composed of hexagonal plates / sheets, and cauliflower-shaped spherulite crystals. The electron microscope image of the carbon layer shows that its morphology is basically the same, so it is preliminarily determined that the densely distributed prisms on the surface of the carbon layer are nano ZnO with a specific structure.
[0207] It can be seen from the above that zinc-containing ionic liquids can not only catalyze the carbonization of polymers to form an expanded flame-retardant carbon layer, but also generate nano ZnO in the flame-retardant process. This material has a stable structure and can further participate in the construction of the flame-retardant carbon layer to form a nano flame-retardant carbon layer, which also provides strong evidence for the high efficiency of such carbon layers. At the same time, this also provides a new idea for the preparation of new nano ZnO. By doping different elements, it is expected to prepare composite materials with special functions such as hybrid nano ZnO. The project team will further explore its possibilities in future research.
[0208] Experimental Example 8: Analysis of morphology of calcined coating
[0209] Fig.83 The morphology of the carbon layer of samples 6 to 8 calcined at 500°C. After calcination at 500°C, it can be found that the coating has expanded, and dense pores can be seen on the cross-section. It has a honeycomb structure. These pores may be filled with carbon dioxide and nitrogen, which can insulate and isolate the outside air to a certain extent, protecting the flame retardant materials from fire and thus playing a flame retardant role. At the same time, these carbon layers are easy to remove from the combustibles after high temperature, which can effectively protect the ancient wooden buildings from burning while protecting their integrity.
[0210] By comparing samples 6-8, it can be found that as the content of zinc-containing ionic liquid increases, the pores become denser, indicating that the increase in the content of zinc-containing ionic liquid can promote the degradation of EA coating to a certain extent, form an expanded carbon layer, and improve its flame retardant effect.
[0211] Fig.84 These are digital photos of the carbon layer of sample 4 calcined at different temperatures. Fig.85 The digital photos of the carbon layer of sample 6 calcined at different temperatures are shown. After calcination at different temperatures, it can be found that sample 4 did not change color before 200°C and maintained its original shape. It began to change color at 210°C, from yellow, orange, red to black carbonization, and then expanded, indicating that the coating of sample 4 had basic flame retardant properties before 200°C, and the coating maintained good flame retardant properties from 210°C to 300°C. The coating began to gradually expand at 300°C, and insulated as much as possible and isolated from the outside air, playing a certain flame retardant effect. Comparing sample 4 and sample 6, it can be found that sample 6 changed color slightly slower than sample 4, indicating that the increase in the content of zinc-containing ionic liquid to a certain extent can promote the flame retardant properties of the coating.
[0212] The present invention uses zinc chloride and acrylamide as raw materials to synthesize zinc-containing active ionic liquid, then mixes it with EA and solidifies it into a coating through UV. The results show that:
[0213] (1) A zinc-containing ionic liquid flame retardant integrating acid source, gas source and carbon source was synthesized using zinc chloride and acrylamide as raw materials, and a series of zinc-containing ionic liquid flame-retardant EA coatings were prepared. Infrared analysis of the thermal degradation products of the coatings showed that the zinc-containing ionic liquid can play a flame retardant role, and the flame retardant effect of the coating increased with the increase of the content of the zinc-containing ionic liquid.
[0214] (2) Zinc-containing ionic liquid can catalyze the carbonization of polymer to form an excellent expanded carbon layer, which has the effect of heat insulation and oxygen isolation, and effectively improves the thermal stability of EA coating.
[0215] (3) Analysis of the flame retardant microstructure shows that Zn(Am)Cl2 has the behavior of low-temperature macroscopic catalytic coating carbonization and high-temperature microscopic catalytic flame retardant. During the flame retardant process, zinc ions gradually transform from free state to bound state to form nano ZnO with different forms. At the same time, the carbon elements in its carbon layer structure exist in a more complex form, which may form a mixture of graphene oxide, graphite oxide and graphite.
[0216] (4) Zn(Am)Cl2 can catalyze the polymer to form an expanded flame-retardant carbon layer, and can also self-catalyze the reaction to generate a nano flame-retardant carbon layer. The two flame-retardant mechanisms promote each other, resulting in the EA coating showing high-efficiency flame-retardant properties.
[0217] (5) As the temperature of the flame retardant coating increases, its cross section changes from being relatively flat to expanding due to heat, and then becoming increasingly irregular, until it becomes smooth, forming an air film, and then an air chamber. At the same time, the expansion of the gas causes the carbon layer to expand and grow until it breaks into needle-like fragments, which are scattered around the air chamber and self-assemble into triangular and hexagonal sheets, which continue to stack and assemble into columns. At nearly 500°C, regular hexagonal ZnO crystals are formed. Its XRD and energy spectrum analysis both prove that hexagonal nano ZnO is generated during the degradation process.
[0218] (6) The carbonization temperature of Zn(Am)Cl2 / EA coating gradually decreases with the increase of flame retardant content.
[0219] (7) The analysis of the microscopic flame retardant structure of Zn(Am)Cl2 / EA coating provides a new method for the preparation of nano-zinc oxide.
[0220] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A method for preparing a zinc-containing ionic liquid, characterized in that: The method comprises: placing acrylamide and p-hydroxyanisole in a round-bottom flask and mixing them evenly, placing the flask in an oil bath, heating the flask to 70-90° C. under magnetic stirring conditions until the reactants in the flask are completely dissolved, adding zinc chloride, continuing heating and stirring for 2-4 hours under condensation reflux conditions, adding acetone solvent, reacting at 60° C. for 3 hours, and vacuum rotary drying at 60° C. after the reaction is completed, so as to obtain a clear and transparent zinc-containing ionic liquid.
2. The method for preparing a zinc-containing ionic liquid according to claim 1, wherein: The mass ratio of acrylamide to zinc chloride is 1:
1.
3. The method for preparing a zinc-containing ionic liquid according to claim 1, wherein: The mass of the p-hydroxyanisole is 0.3% of the mass of acrylamide.
4. A method for preparing a Zn-containing multi-layered high-efficiency synergistic flame-retardant epoxy acrylic coating, characterized in that: The method comprises: sequentially stirring the zinc-containing ionic liquid prepared by the method for preparing the zinc-containing ionic liquid according to any one of claims 1 to 3, epoxy acrylate resin, and photoinitiator, heating and ultrasonically oscillating until bubbles are eliminated, and stirring into a uniform solution, uniformly coating the prepared uniform solution on a coating carrier, and curing by light to obtain a Zn-containing multi-layered high-efficiency synergistic flame-retardant epoxy acrylate coating.
5. The method for preparing the Zn-containing multi-layered high-efficiency synergistic flame-retardant epoxy acrylic coating according to claim 4, characterized in that: The mass ratio of the zinc-containing ion liquid, epoxy acrylic resin and photoinitiator is 1.0-7.0:4.8-5.2:0.2-0.
3.
6. A Zn-containing multi-layer high-efficiency synergistic flame-retardant epoxy acrylic coating, characterized in that: The Zn-containing multi-layered high-efficiency synergistic flame-retardant epoxy acrylic coating is prepared by the preparation method of the Zn-containing multi-layered high-efficiency synergistic flame-retardant epoxy acrylic coating according to any one of claims 4 to 5.